(untitled) (Quest Journal of Management and Social Sciences, 2022)
Background: Staff retention has always been a significant concern as well as a challenge for all sectors of organizations. This work aims to identify the major factors that serve as determinants of staff retention, specifically in the hotel industry. The work has been solely guided to establish a conceptual framework that could be used for the systematic and objective investigations to be initiated in the future in this particular sector of the specialized economy. Methodology: Since this study is entirely thematic desk research-based, the present scribe has used exploratory research by comprehending different influencing factors of staff retention that were assessed through the review of various lead articles, policy guidelines, related published research reports, conceptual perspectives available in other sources, and institutional best practices in the global arena. Results: The overall findings of the study reveal that the factors including the prevalence of two-way communication, style and quality of leadership, autonomy at the job, motivation level, involvement at work, organizational support, performance management, work-life balance, level of involvement in decision-making, career growth opportunity, availability of training and development opportunities, organizational culture, valuable inputs and constructive feedbacks, trade union and employer agreements, staff recruited from employment agencies and compensation package serve instrumental in the retention of staff. Additionally, this work has established the staff perceived level of glamour and lifestyle, job prestige, social recognition, and opportunity for learning and growth as the industry matched valences. Conclusions: The study concludes that in addition to several conventional factors affecting staff retention in different sectors, the tradition of scientific inquiry in the hotel industry should also focus on exploration of the shared impact of more innovative constructs, including state of glamour and lifestyle, social recognition, personal branding, opportunities for cross-cultural learning. Implications: The present work would serve as instrumental for the new generation of researchers to craft more innovative and suitable research areas with a balance of constructs to be observed. Similarly, this work establishes a stock of resources to be used in the academic discourses aimed at exploring determinants of staff retention with a specific focus on the hospitality industry, particularly the hotel sector. Also, the management in the respective industry may find suitable ways forward to adjust their organizational process climate and culture to retain the valuable staff.